Interaction of CO2 and CH4 with Functionalized Periodic Mesoporous Phenylene-Silica: Periodic DFT Calculations and Gas Adsorption Measurements - Lourenco, Mirtha A. O.
Nonfunctionalized and functionalized periodic mesoporous phenylene-silicas (Ph-PMOs) with different kinds of amine groups were prepared and their capacity to uptake CO2 and CH4 molecules were experimentally evaluated considering biogas upgrading. It was found that aminopropyl groups grafted to the free silanols of the Ph-PMO displayed the highest selectivity for CO2 gas, adsorbing 26.1 times more CO2 than CH4 at 25 degrees C. The interaction effect of the surface of these materials with the CO2 or CH4 molecules was obtained through the calculation of the Henry constants, and the adsorption mechanisms involved were elucidated from density functional theory calculations. The good synergy between experimental gas adsorption and computational studies suggests that the latter can be used to guide the experimental synthesis of more effective materials. Thus, our computational studies were extended to PMOs with other functional groups having different polarity for predicting interaction energies with CO2 and thus identifying the most promising candidates for experimental synthesis.